Russian Federation : 2020 Article IV Consultation-Press Release; Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Russia entered the crisis with low potential growth but strong macroeconomic policy frameworks and significant buffers. Policy space allowed the authorities to mount a sizeable public health and countercyclical response to the crisis, which has helped limit the economic downturn. Nevertheless, the crisis is likely to leave some long-term scars.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Russian Federation